Improving the Management of International Supply Chains on the Basis of a Logistic Conception - Pysmak Viktoriia O. (Bìznes Inform, 2019)
The article discusses the theoretical principles of the management of supply chains in terms of international contacts on the basis of application of a logistic conception. The concept of the international supply chain is clarified, the basic variants of its building are researched. The publication argues that logistic providers create preconditions for more efficient performance of business processes. It is proved that the organization of multimodal transportations of goods in the international supply chains should include harmonization of the overall characteristics of the cargo units on the basis of logistic accounting and contractual units, simplification of customs formalities and presence of a single person responsible to the owner. Features of the main technologies of cargo transportation in the international cooperation are considered and recommendations on increase of efficiency of each of them on the basis of application of a logistic conception are suggested.